2022
DOI: 10.1111/jth.15890
|View full text |Cite
|
Sign up to set email alerts
|

Achieving higher efficacy without compromising safety with factor XI inhibitors versus low molecular weight heparin for the prevention of venous thromboembolism in major orthopedic surgery—Systematic review and meta‐analysis

Abstract: Background: In recent years, many important advances have been seen in anticoagulation therapy. However, bleeding risk is still a major concern. Factor XI (FXI) inhibition has emerged as a potential advantageous target to minimize this risk. Objectives:We conducted a systematic review and meta-analysis of current evidence on FXI inhibitors for thromboprophylaxis in major orthopedic surgery. Methods:We performed a systematic search of electronic databases (PubMed, CENTRAL, and Scopus) until May of 2022. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Our analysis confirms that FXI inhibitors are associated with superior safety and efficacy compared with LMWH but suggests that the superior safety may be driven by a reduction of minor bleeding with no difference in major bleeding. These results are in line with other recent contributions on patients with recent knee arthroplasty surgery (27,28). PACIFIC-AF compared the small molecule asundexian at the dose of 20 mg or 50 mg od with apixaban 5 mg bid in 755 patients with AF and an indication for OAC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our analysis confirms that FXI inhibitors are associated with superior safety and efficacy compared with LMWH but suggests that the superior safety may be driven by a reduction of minor bleeding with no difference in major bleeding. These results are in line with other recent contributions on patients with recent knee arthroplasty surgery (27,28). PACIFIC-AF compared the small molecule asundexian at the dose of 20 mg or 50 mg od with apixaban 5 mg bid in 755 patients with AF and an indication for OAC.…”
Section: Discussionsupporting
confidence: 88%
“…These results are in line with other recent contributions on patients with recent knee arthroplasty surgery. 27 28 PACIFIC-AF compared the small molecule asundexian at the dose of 20 or 50 mg od (once daily) with apixaban 5 mg bid in 755 patients with AF and an indication for OAC. Both doses of asundexian resulted in lower rates of bleeding compared with standard dosing of apixaban, with similar efficacy in the three treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis focusing on trials with patients undergoing total knee replacement showed that factor XIa inhibitors were associated with a significantly lower incidence of total VTE (14.5 vs. 23.6%; odds ratio [OR] ¼ 0.50; 95% confidence interval [CI]: 0.36, 0.69; p 0.001) in comparison to LMWH, with the incidence of composite major and clinically relevant nonmajor (CRNM) bleeding events being significantly lower (1.6 vs. 3.2%, OR ¼ 0.41; 95% CI: 0.22, 0.75; p ¼ 0.003). 15 A subsequent sensitivity analysis demonstrated that higher doses of factor XIa inhibitors when grouped together (namely, abelacimab: 75 and 150 mg; FXI-ASO: 300 mg; milvexian: 50 mg twice daily, 100 mg twice daily, 200 mg daily, and 200 mg twice daily and 1.8 mg/kg of osocimab of preoperative administration) are more efficacious in preventing symptomatic or asymptomatic VTE as a composite outcome compared with LMWH, without significantly increasing the occurrence of major and CRNM bleeding as a composite outcome. Another grouped analysis focusing only on lower doses of XIa inhibitors (abelacimab: 30 mg; FXI-ASO: 200 mg; milvexian: 25 mg once daily, 25 mg twice daily, and 50 mg once daily; 0.3 mg/kg of preoperative administration of osocimab; 0.3, 0.6, and 1.2 mg/kg postoperative administration of osocimab) showed significantly lower bleeding events, but without the effectiveness seen in higher doses.…”
Section: Results From Phase II Clinical Trialsmentioning
confidence: 99%
“…Another grouped analysis focusing only on lower doses of XIa inhibitors (abelacimab: 30 mg; FXI-ASO: 200 mg; milvexian: 25 mg once daily, 25 mg twice daily, and 50 mg once daily; 0.3 mg/kg of preoperative administration of osocimab; 0.3, 0.6, and 1.2 mg/kg postoperative administration of osocimab) showed significantly lower bleeding events, but without the effectiveness seen in higher doses. 15 In 2022, the results from three major international, double-blinded Phase II trials with asundexian for patients with atrial fibrillation (AF), recent stroke, or recent Table 1 Mechanism of action and pharmacokinetics of factor XIa inhibitors A Review of FXIa Inhibition as a Novel Target for Anticoagulation Koulas, Spyropoulos 31…”
Section: Results From Phase II Clinical Trialsmentioning
confidence: 99%
“…For clinically significant bleeding, the OR was 0.41 (95% CI 0.22-0.75). The risk for VTE episodes in the study patients treated with LMWH was estimated at 23.6%, and that for major or clinically significant bleeding at 3.2% [13].…”
mentioning
confidence: 94%